The importance of biome in shaping urban biodiversity - Diamant, E.S.; Oswald, K.N.; Awoyemi, A.G.; Gaston, K.J.; MacGregor-Fors, L.; Berger-Tal, O.; Roll, U. (Elsevier, 2025)
Humanity is urbanizing, with vast implications on natural systems. To date, most research on urban biodiversity has centered on temperate biomes. Conversely, drylands, collectively the largest terrestrial global biome, remain understudied. Here, we synthesize key mechanistic differences of urbanization's impacts on biodiversity across these biomes. Irrigation shapes dryland urban ecology, and can lead to greener, sometimes more biodiverse, landscapes than local wildlands. These green urban patches in drylands often have a different species composition, including many non-native and human-commensal species. Socioeconomic factors – locally and globally – can mediate how biomes shape urban biodiversity patterns through the effects of irrigation, greening, and invasive species. We advocate for more research in low-income dryland cities, and for implementing biome-specific, scientifically grounded management and policies.